Approximate number sense theory or approximate theory of magnitude?. (2017) - Content, Alain; Velde, Michael Vande; Adriano, Andrea
Abstract: Leibovich et al. argue that the evidence in favor of a perceptual mechanism devoted to the extraction of numerosity from visual collections is unsatisfactory and propose to replace it with an unspecific mechanism capturing approximate magnitudes from continuous dimensions. We argue that their representation of the evidence is incomplete and that their theoretical proposal is too vague to be useful.